About hyperthyroid states and their treatment - Odriozola, Ernesto (1919)
Our distinguished friend, Dr. M GONZALEZ OLAECHEA has had the finesse to send the patient who is now going to deal. Needless to add them I think we sent him his just and comprehensive diagnostic label. Being a special clinical category and item are sick deserves a lengthy study because the interest is apparent contemplation give presents multiple diagnoses postulates that it is essential to analyze, to go back to the real cause now shines univocal thanks to the great progress of endocrinology.